Are South African directors able to earn abnormal returns by trading in their companies shares? - Ismail, Ameera (Department of Finance and Tax, 2016)
This paper investigates whether South African directors are able to earn abnormal returns by trading in their companies' shares. An event study methodology was used based on the Capital Asset Pricing Model for director's trades during the period 2009 to 20 12. The results suggest sales transactions are associated with a greater market reaction than purchases. A better market indication is received from in directly beneficial trades than directly beneficial, specifically for sales. Upon further analysis, we find significantly higher abnormal returns for larger value trades. For purchases, single director trades provide a stronger market reaction than multiple director trades. In contrast, sales transactions provide a stronger signal when they are from multiple directors than single directors